Collaural fistula (Work Type II first branchial cleft anomaly) with prolonged morbidity: A case report. (May 2021) - Penjor, Dorji; Kitamura, Morimasa
Collaural fistula is a very rare Work Type II first branchial cleft anomaly in which there is a complete fistulous tract between external auditory canal and the neck. Misdiagnosis and mismanagement can lead to prolonged morbidity and complications due to repeated infections. We present a case of an 18-year-old lady with a recurrent discharging sinus on her neck for 4 years. She has been treated with repeated incision and drainage and multiple antibiotics in the past. Otoscopic examination revealed an opening on the floor of the left external auditory canal. A diagnosis of an infected collaural fistula was made. Complete excision of the fistulous tract was done after treatment of the active infection. On follow-up, there was no further recurrence at 1 year. Sound knowledge of embryology of branchial anomalies with good history and examination is important to make correct and early diagnosis to prevent morbidity.